ESTIMATION OF TOTAL PHENOL IN SOME MEDICINAL PLANTS OF MARATHWADA REGION IN MAHARASHTRA - Kadam, V B; SONAWANE, V B; TAMBE, S S; KADAM, U B (Journal of Drug Delivery and Therapeutics, 2013)
An  attempt  has  been  made  here  to  investigate  occurrence  of  total  phenol in  the leaves , bark  and  wood   of  Butea monosperma Lam, Madhuca  indica Gmel,  Mimusops elengi Linn and Syzygium cumini Linn. are medicinally important plants of Marathwada region in Maharashtra. Comparative  account  of  total  phenol  content  of  leaves ,bark and wood of  four  species  revealed  that , Madhuca  indica were  rich  ( range 2.156  to 4.410  mg / g dry wt. )  than Butea monosperma (range 1.987 to 4.138 mg / g dry wt.) , Mimusops elengi (range 2.601 to 3.438 mg / g dry wt.)  and Syzygium cumini (range 1.621 to 3.330  mg / g dry wt. )  in all seasons. Key words:  Total Phenol, Medicinal Plants, Marathwada region.